Effect of fiber content variation on the strength of the weakest section in Strain Hardening Cementitious Composites (SHCC). (15th June 2017) - Lu, Cong; Leung, Christopher K.Y.
Highlights: A numerical approach is proposed which distributes fibers randomly. The bridging law in a section is correlated with all nearby fibers and thus changes continuously. A size effect on the fiber content variation between sections is revealed. Abstract: Fiber dispersion, especially the variation of fiber content among different sections of a member, is a major factor that influences the mechanical properties of fiber composites. In this study which focuses on Strain Hardening Cementitious Composites (SHCC), a numerical approach is proposed to compute the bridging laws in various sections of a specimen with varying content of randomly distributed fibers. Through the analysis, the weakest plane which governs the ultimate strength and saturated crack spacing is determined. This weakest plane is then investigated for members of different sizes, and a size effect is revealed.